ACETS OF INHALATIONAL MIDAZOLAM IN STATUS EPILEPTICUS - MATHIAZHAGAN, SANGAVAI; S, ANAND; T, MEENAKSHI (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Status epilepticus (SE) is a medical emergency associated with significant morbidity and mortality. SE is defined as a continuous seizure lasting more than 30 minutes, or two or more seizures without full recovery of consciousness between any of them. Early treatment of SE with benzodiazepines, followed if necessary by fosphenytoin administration, is the most widely followed strategy. In developing countries where facilities for assisted ventilation are not readily available, it may be helpful to use inhalational midazolam in such settings. It is important to recognize SE and institute treatment as early as possible to avoid a refractory state. It is equally important to attend to the general condition of the patient and to ensure that the patient is hemodynamically stable. Keywords: Epilepsy, Nasal route, Midazolam, Inhalational route, Facets.